Upaya Mewujudkan Program Kampus Merdeka Pada Kurikulum PGMI STIT Al Ittihadiyah Labuhanbatu Utara - Muhammad Shaleh Assingkily (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Abstract: The development of science and technology, the challenges of the quality of institutions, and skills in the 21st century are the main reasons for the need for an independent learning campus curriculum. This is an opportunity as well as a challenge for higher education institutions in producing quality human resources. This article aims to analyze efforts to realize an independent-campus learning curriculum in the PGMI STIT Al Ittihadiyah study program, North Labuhanbatu. The focus of this article's discussion is on the campus's efforts in realizing an independent campus curriculum. This study uses a qualitative approach to field research methods. Data collection was carried out by using online interview techniques using WhatsApp and document review. Through this research, it was found that the efforts made by the campus in realizing an independent campus (independent learning) were (1) Aligning the profile of graduates with the needs of society, (2) Determining approaches, strategies, and methods of learning by community demands, (3) Determining types and assessment techniques and (4) maps of curriculum alignment including Learning Outcomes (CPL), materials, methods, and assessment.